The missing sister - Marr, Elle (Thomas & Mercer, 2020)
"In Paris, her twin sister has vanished, leaving behind three chilling words: Trust no one. Shayna Darby is finally coming to terms with her parents' deaths when she's delivered another blow. The body of her estranged twin sister, Angela--the possible victim of a serial killer--has been pulled from the Seine. Putting what's left of her life on hold, Shayna heads to Paris. But while cleaning out Angela's apartment, Shayna makes a startling discovery: a coded message meant for her alone ... Alive. Trust no one. Taking the warning to heart, Shayna maintains the lie. She makes a positive ID on the remains and works to find out where--and why--her missing sister is hiding. Shayna retraces her sister's footsteps, and they lead her down into Paris's underbelly. As she gets closer to the truth--and to the killer--Shayna's own life may now be in the balance ..."--FantasticFiction.com.